2019
DOI: 10.1097/xeb.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

The fragility of randomized trial outcomes underlying management of dyspepsia and Helicobacter pylori infections

Abstract: Aim: The fragility index is calculated by changing one outcome event to a nonevent within a trial until the associated P value exceeds 0.05. In this study, we assessed the robustness, risk of bias (RoB), and power of randomized controlled trials that underlie recommendations set forth by the American College of Gastroenterology (ACG) on managing dyspepsia and Helicobacter pylori infections. Methods: All citations referenced in the guidelines were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The inclusion criteria for the guidelines concerned: (1) adults; (2) with dyspepsia as defined by the Rome III or IV criteria; (3) the management and treatment strategy; (4) the presence of HP; (5) the guidelines available online, (6) in English or French languages; (7) developed at the national level by gastroenterological societies or health authorities (such as HAS and DGVS and others) and at the international level upon expert consensus.…”
Section: Selection Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion criteria for the guidelines concerned: (1) adults; (2) with dyspepsia as defined by the Rome III or IV criteria; (3) the management and treatment strategy; (4) the presence of HP; (5) the guidelines available online, (6) in English or French languages; (7) developed at the national level by gastroenterological societies or health authorities (such as HAS and DGVS and others) and at the international level upon expert consensus.…”
Section: Selection Criteriamentioning
confidence: 99%
“…Many CPGs, that differ among themselves and are not necessarily of good quality, discuss the link between an HP infection and functional dyspepsia. In 2019 for example, Meyer et al questioned the quality of randomized trials on which the guidelines were based 5–7 . They showed that of the fourteen guidelines defined by the American College of Gastroenterology (ACG) on the management of dyspepsia, eight were based on data of low or very low level of evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation